Mesenchymal stromal cells: clinical challenges and therapeutic opportunities - Galipeau, Jacques (Cell Stem Cell, 2018)
Mesenchymal Stromal Cells (MSCs) have been the subject of clinical trials for more than a generation and the outcomes of advanced clinical trials have fallen short of expectations raised by encouraging pre-clinical animal data in a wide array of disease models. In this perspective, important biological and pharmacological disparities in pre-clinical research and human translational studies are highlighted, and analysis of clinical trial failures and recent successes provide a rational pathway to MSC regulatory approval and deployment for disorders with unmet medical needs.